(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The easy access to information and knowledge offers several advantages to various factors like the socio-economic environment where individuals, who can obtain news more rapidly, access services more easily and perform on-line commercial and banking transactions; enterprises, which has ability to develop innovative products and services that makes user satisfied. We can achieve competitive advantages from effective use of the knowledge gained; the public administration, which can improve the services provided to citizens using e-government applications, such as on-line payments of tax contributions, and e-health tools, by considering each patient’s medical history, thus improving the quality of healthcare services. The enterprises that are capable of transforming data into information and knowledge can use them to make quicker and more effective decisions and thus to achieve a competitive advantage. it is possible today to extract from the huge amounts of data available, knowledge which can then be used by decision makers to aid and improve the governance of the enterprises and the public administration. Companies have realized the importance of imposing achievements of the goals defined by their business strategies through business intelligence concepts. It defines the visions on the role and requirement of real time BI by studying the business needs. The paper explores the concepts of BI, its components, BI methodology, Decision Making using and forecasting using BI and BI tools available for Decision Making and business forecasting